Influence of residual chlorine and pressure on the degradation of water pipes of polyethylene of raised temperature. (December 2021) - Fujii, Takehiro; Hirabayashi, Hideo; Matsui, Yuichi; Igawa, Kazushisa; Honma, Hidekazu; Yamada, Kazushi
Highlights: Accelerated degradation tests were conducted for PE-RT pipe. Influence of residual chlorine and pressure on degradation of PE-RT pipe are examined. The degradation of the PE-RT pipe was promoted by chlorine derivatives. In the degradation of PE-RT pipe, the change in fluorescence spectrum showed a similar trend to the I-OIT results. Abstract: A simple and accurate evaluation of the degradation of polymeric products, which are indispensable parts of our daily life, is important for the safe and long-term use of these products. Herein, we present a novel evaluation method for the pipes of polyethylene of raised temperature (PE-RT), a non-cross-linked polyethylene. In this method, we conducted accelerated degradation tests using a custom-designed small pressure vessel. Although it is known that residual chlorine in tap water accelerates the degradation of plastic pipes, this method reveals that the water pressure further accelerates the degradation of the pipes. We demonstrate for the first time that the results of three-dimensional fluorescence spectral studies exhibit a similar trend as those of the conventional isothermal oxidation induction time (I-OIT) measurement. This fluorescence-based method can contribute to the development of new evaluation methods to study plastic degradation, because it is very simple, does not require sample pretreatment, unlike I-OIT and other degradation evaluation methods, and the measurement can be performed directly within a few minutes.